Public Employment and Redistributive Politics: Evidence from Russia's Regions - Vladimir Gimpelson; Daniel Treisman; Galina Monusova (Journal of Economic Sociology, 2010)
Public employment grew surprisingly fast in Russia during the 1990s, at a time when total employment was falling. Most of this growth occurred in the country's 89 regions, and rates varied among them. This paper seeks to explain this variation. Using panel data for 78 regions over 1992-1998 we test several hypotheses. We show that the increase in the share of public employment in total employment has been greatest where unemployment was highest and growing the fastest, in ethnically defined territorial units, and in regions which received larger federal transfers and loans. Regional governors appear to use public employment for several purposes: as a kind of economic insurance to cushion the population against unemployment; as a way of buying votes before elections; and, possibly, as a way of redistributing to minority ethnic groups. Their willingness to use it for any of these is conditioned by the level of federal financial aid they can attract. The paradoxical growth of public employment in Russia appears less a result of ignorant or irresolute central management than a perverse outgrowth of the competitive game of federal politics, in which regional governors use public sector workers as "hostages" to extract transfers.